Degenerescência Macular da Idade (DMI) - Guidelines de Tratamento 2018 - Teixeira, Carla C; Furtado, Maria João; Carneiro, Angela; Silva, Rufino (Revista Sociedade Portuguesa de Oftalmologia, 2018)
Degenerescência Macular da Idade (DMI) - Guidelines de Tratamento 2018